1991
DOI: 10.1016/0014-5793(91)80186-7
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the role of the S4 substrate binding site of HIV proteinases

Abstract: Kinetic una )'sis of the hydrtd~sis of the I~ptide lI.Val,Ser.GIn,Asn.Tyr*Pro.ll¢.VaI.GIn.Nll~ and its analo$,t obtainctl by varyinll the !ength and introduein= substitutions at the P, site was carried out with t~flh HIV.I and ItlV.2 prolein~se~. Deletion or ih¢ t~rmlnal Vtd ~nd Gin had only metier|tie effect on ilia ~uhstrltte hydroly~h, while the d~lation of tli.c P.~. Set ~ts well as P; V,I Ilrcatly reduwd the substrata hydrolysis. Thi~ is pr~dicled to bc due to the loss of Intera,:tions betwoen main ~h~ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 23 publications
(9 reference statements)
1
38
0
Order By: Relevance
“…Indeed, the specificity constants for the ACC substrates are at least 3 orders of magnitude lower than those for longer substrates. That ACC proteolysis is measurable runs contrary to the findings of prior studies that have shown the minimal length of an HIV PR substrate to be P4 to P3Ј (10,42). However, specificity constants this low would be extremely difficult to measure using the detection methods typically used with HIV PR, which often involve high-pressure liquid chromatographic analysis and/or the use of a less-sensitive chromogenic or fluorogenic reporter group.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Indeed, the specificity constants for the ACC substrates are at least 3 orders of magnitude lower than those for longer substrates. That ACC proteolysis is measurable runs contrary to the findings of prior studies that have shown the minimal length of an HIV PR substrate to be P4 to P3Ј (10,42). However, specificity constants this low would be extremely difficult to measure using the detection methods typically used with HIV PR, which often involve high-pressure liquid chromatographic analysis and/or the use of a less-sensitive chromogenic or fluorogenic reporter group.…”
Section: Discussionmentioning
confidence: 60%
“…However, all three libraries showed a strong tendency toward small residues. Similarly, a preference for small amino acids such as serine in this position has been reported (42).…”
Section: Specificity Of Hiv Prmentioning
confidence: 66%
“…It is important to note that this shorter peptide showed 10-fold higher k cat and k cat /K m values than peptide 16. The effect of residues P 5 and P 4 on substrate hydrolysis has been reported previously (11,23). To compare the specificity of the S 3 and S 3 Ј substrate binding pockets in an identical sequence context, the Asp residues of the palindromic peptide 17 were substituted to Gly, Gln, Phe and Leu residues (Table III).…”
Section: Substitutions In a Palindromic Substrate Sequencementioning
confidence: 97%
“…In addition, peptide 2 also contains Thr at both P 2 and P 2 Ј positions. Furthermore, peptides 1 and 2 with the exception of the P 2 Ј residues share the same sequence in the P 4 -P 3 Ј region, which is the major determinant for specificity (23). However, peptide 2 was found to be a much poorer substrate of the HIV proteinases than peptide 1 (see Table I and Ref.…”
Section: Substitution Of Amino Acids Of a Type 1 Cleavage Site Peptidmentioning
confidence: 99%
See 1 more Smart Citation